Assessment of the efficiency of innovative reagents for purification of water from the Sava River (Belgrade): Original scientific paper - Kuzin, Evgenii Nikolaevich (HEMIJSKA INDUSTRIJA (Chemical Industry), 2026)
There is a growing focus on enhancing environmental safety in Serbia. The development of hydrosphere protection technologies is one of the priority tasks, the solution of which will considerably improve the quality of life for the population and bring the country closer to the EU standards. The Sava River is one of the largest waterways running through Belgrade. In this work it was shown that the use of complex titanium-containing coagulants allows not only for the efficient removal of dispersed particles from water and a 70 % reduction in organic compound content, but also a 66 % decrease in the level of microbiological contamination. The use of sodium ferrate, a coagulant and bactericide, allows for a significant reduction of pollutant content in water as well as complete water decontamination. It was demonstrated that the use of a complex titanium-containing reagent considerably increases the sedimentation rate of coagulation sludge by 20 to 30 % and the filtration rate by 10 to 20 %.